1992
DOI: 10.1016/0735-1097(92)90094-4
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and mortality rate of congestive heart failure in the United States

Abstract: Congestive heart failure is a common problem in the U.S., with significant prevalence and mortality, both of which increase with advancing age. As the population of the U.S. becomes older, the health care impact of congestive heart failure will probably grow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
334
1
16

Year Published

1998
1998
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 741 publications
(365 citation statements)
references
References 23 publications
14
334
1
16
Order By: Relevance
“…All subjects were referred to the arrhythmia unit with complaints of palpitations. Subjects were separated into three groups according to severity of heart involvement by the Los Andes classification (15): class I = 14 subjects, class II = 24 subjects, and class III = 12 subjects. Clinical and laboratory data were assessed during a personal interview and by review of the medical records.…”
Section: Methodsmentioning
confidence: 99%
“…All subjects were referred to the arrhythmia unit with complaints of palpitations. Subjects were separated into three groups according to severity of heart involvement by the Los Andes classification (15): class I = 14 subjects, class II = 24 subjects, and class III = 12 subjects. Clinical and laboratory data were assessed during a personal interview and by review of the medical records.…”
Section: Methodsmentioning
confidence: 99%
“…According to Hermann and Greenberg 5 , however, it is not known if this reflects a difference in the natural history of the disease or if it results from the influence of the underlying etiology or from gender-dependent res-ponse to treatment. Schocken et al 6 , in another population study, also found smaller mortality in women. In Chagas' disease, the male patients, who have greater impairment in ejection fraction (EF), also have the poorest prognosis compared to women 7,8 .…”
Section: The Role Of Gendermentioning
confidence: 84%
“…Independently from the risk of developing CAD, diabetes increases the risk of developing CHF, and this risk is at least double in women than in men 6,17 . The risk of CHF is increased five times when hypertension is associated with diabetes 5 .…”
Section: Presence Of Comorbiditymentioning
confidence: 99%
See 1 more Smart Citation
“…Left ventricular systolic dysfunction (LVSD) and impaired pulmonary function (IPF) are associated with significant morbidity and mortality,1, 2, 3, 4, 5, 6, 7 and prevalence of both conditions increases with age 1, 5, 8, 9, 10. While cardiovascular disease is a major cause of death in individuals with IPF,7 little is known about the relative impact and the joint association of LVSD and IPF in terms of risk for clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%